THE ROLE OF ACEHNESE ULAMA IN THE SUFISM, TAUHID, AND FIQH STUDY MOVEMENT: Historical and Contextual Perspectives - Buto Siregar, Zulfikar Ali; Muhibuddin, Muhibuddin Muhibuddin; Mohd Jamil, Mohd Ridhuan (UIN Sumatera Utara, 2025)
This study examines the development of Tasawuf, Tauhid, and Fiqh in Acehnese society, focusing on the contributions of local scholars. Using a qualitative approach, it explores the interrelation of these Islamic disciplines and their influence on religious practices. The findings highlight the scholars' role in disseminating these studies through traditional institutions such as dayah (Islamic boarding schools), mosques, meunasah, balee, and even local cafés. The integration of Tasawuf, Tauhid, and Fiqh is crucial in shaping Aceh's religious identity. This movement is further reinforced by the establishment of TASTAFI, an organization formed by dayah alumni, which has expanded across districts in Aceh.